PENGARUH MODEL COOPERATIVE INTEGRATED READING AND COMPOSITION (CIRC) BERBANTUAN MEDIA FLIPBOOK TERHADAP KEMAMPUAN MEMBACA PEMAHAMAN KELAS V PADA PEMBELAJARAN BAHASA INDONESIA DI SEKOLAH DASAR - Shanata Pratiwi; Ahmad Syarif; Desy Rosmalinda (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The purpose of this study was to determine how the implementation of the Cooperative Integrated Reading and Composition (CIRC) model with the aid of flipbooks impacts the reading comprehension skills of fifth-grade students in Indonesian language learning in elementary schools. This study was conducted at SDN 197/IV, Jambi City, in the 2025/2026 academic year and used a quantitative approach. This approach employed a nonequivalent control group design involving two groups: an experimental group and a control group. The data collection method used a reading comprehension test. The results showed that the implementation of the CIRC model with the aid of flipbooks had a significant effect on students' reading skills. The Mann–Whitney U test showed a significance value of 0.001 <0.05. The Wilcoxon test results for the experimental class obtained a significance value of 0.000 <0.05, while the significance value for the control class was 0.053 >0.05. Consequently, Ha was accepted, and Ho was rejected. The results indicate that the reading skills of fifth-grade elementary school students were influenced by the CIRC model